Molecular Triad Containing a TEMPO Catalyst Grafted on Mesoporous Indium Tin Oxide as a Photoelectrocatalytic Anode for Visible Light‐Driven Alcohol Oxidation. Issue 14 (22nd June 2021) - Pati, Palas Baran; Abdellah, Mohamed; Diring, Stéphane; Hammarström, Leif; Odobel, Fabrice
Abstract: Photoelectrochemical cells based on semiconductors are among the most studied methods of artificial photosynthesis. This study concerns the immobilization, on a mesoporous conducting indium tin oxide electrode (nano‐ITO), of a molecular triad (NDADI−P−Ru‐TEMPO) composed of a ruthenium tris‐bipyridine complex (Ru) as photosensitizer, connected at one end to 2, 2, 6, 6‐tetramethyl‐1‐piperidine N‐oxyl (TEMPO) as alcohol oxidation catalyst and at the other end to the electron acceptor naphthalenedicarboxyanhydride dicarboximide (NDADI). Light irradiation of NDADI−P−Ru‐TEMPO grafted to nano‐ITO in a pH 10 carbonate buffer effects selective oxidation of para ‐methoxybenzyl alcohol (MeO−BA) to para ‐methoxybenzaldehyde with a TON of approximately 150 after 1 h of photolysis at a bias of 0.4 V vs. SCE. The faradaic efficiency is found to be of 80±5 %. The photophysical study indicates that photoinduced electron transfer from the Ru complex to NDADI is a slow process and must compete with direct electron injection into ITO to have a better performing system. This work sheds light on some of the important ways to design more efficient molecular systems for the preparation of photoelectrocatalytic cells based on catalyst‐dye‐acceptor arrays immobilized on conducting electrodes. Abstract : Triad and true : A photoelectrochemical cell is assembled based on a dye, an electron acceptor and an alcohol oxidation catalyst (TEMPO) grafted on a mesoporous conducting ITO electrode. Upon light irradiation, methoxybenzyl alcohol is oxidized into methoxybenzaldehyde in a carbonate buffer with a turnover number of around 150 at a bias of 0.4 V vs. SCE and a faradaic efficiency of 80 %.